Pemberlakuan Living Law pada Masyarakat Bromo Tengger Semeru di Wilayah Tosari Kabupaten Pasuruan berdasarkan Jangkauan Asas Legalitas KUHP Nasional - Wiwin Ariesta; Ahmad Sukron; Khansa Kamila Aurelia Putri (Lembaga Teewan Journal Solutions, 2026)
The enactment of Law Number 1 of 2023 concerning the new Indonesian Criminal Code (KUHP Baru), effective in January 2026, introduces the recognition of “Living Law” under Article 2, marking a significant shift from the colonial legacy of the previous code. This recognition has sparked debate among legal scholars, particularly regarding its potential inconsistency with the long-established principle of legality. Although the 1945 Constitution and Law Number 6 of 2014 on Villages acknowledge customary law communities, formal recognition by the state remains a prerequisite for exercising customary justice. This study examines the application of Living Law within the Tengger Bromo Semeru community in Tosari District, Pasuruan Regency, which strongly upholds its customary norms. Employing a normative juridical method supported by empirical approaches, this research analyzes both current practices and future implementation post-KUHP Baru. The findings reveal that the application of Living Law is strictly limited by ideological, human rights, formal, territorial, justice, and sanction boundaries. Notably, formal limitations require the codification of customary norms into regional regulations (Perda) to ensure legal certainty. Without such codification, customary sanctions risk being deemed unlawful, thereby undermining their legitimacy within the national legal system while emphasizing the necessity of state recognition and legal integration